PEMBELAJARAN CONTROVERSIAL ISSUES DALAM MENINGKATKAN KEMAMPUAN KOGNITIF MAHASISWA PADA MATA KULIAH KAPITA SELEKTA SEJARAH INDONESIA - Suwarni Suwarni; Emusti Rivasintha; Yuver Kusnoto (Universitas Muhammadiyah Purwokerto, 2018)
The general objective in this research is "to know the application of controversial issue model in improving cognitive ability in Kapita Selekta Sejarah Indonesia courses". This reseach used classroom action research method. Located at Prodi Pendidikan Sejarah IKIP PGRI Pontianak. Subject of research were student that requires 22 people. The design of this research consists of planning, implementation, observation and reflection. Data completion technique used is direct observation, measurement, and documentary. Application of controversial learning model showing the result that it can improve students' cognitive abilities in Kapita Selekta Sejarah Indonesia. Planning the application of controversial issue model to improve students cognitive ability in Kapita Selekta Sejarah Indonesia courses in Prodi Pendidikan Sejarah IKIP PGRI Pontianak, has been done well. This is indicated by the learning process run in accordance with the implementation plan of learning. The material presented by the lecturer attract the attention of the students. The steps of learning model controversial issue has been done well. There are student activeness in asking and replied and they are breave to expressed his opinion throught answer issues that were given. The time allocation goes as planned. Keywords: controversial issues, history learnings, cognitive abillity